Terms of Reference: Genebank Platform Evaluation - CGIAR Independent Advisory and Evaluation Service (2023)
Through the Genebank Platform, CGIAR genebanks managed collections of more than 20 staple crops in 12 locations on five continents. The collections remain freely available upon request to thousands of users worldwide under the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA), accounting for a large amount of the germplasm exchanged every year under the multilateral system of access and benefit sharing. CGIAR genebanks safeguard some of the largest and most widely used collections of crop diversity in the world, critical to attaining global development goals to end hunger and improve food and nutrition security. The genebanks- as a key driver of the international exchange of Plant Genetic Resources for Food and Agriculture (PGRFA)-are fundamental to delivering the CGIAR 2030 Research and Innovation Strategy.